Vitreous penetration of levofloxacin in the uninflamed phakic human eye. Issue 4 (1st April 2002) - Herbert, E N; Pearce, I A; McGalliard, J; Wong, D; Groenewald, C
Abstract : Aims: To assess the vitreous penetration of oral levofloxacin (a new fluoroquinolone antibiotic with improved Gram positive activity) in uninflamed phakic eyes. Methods: 15 patients for macula hole surgery were recruited to the study. 10 received a single 500 mg dose of levofloxacin by mouth preoperatively. Five acted as controls. Serum and undiluted vitreous samples were obtained at surgery and analysed by HPLC. Results: Levofloxacin was detectable 2.5 hours after administration in the vitreous. A peak concentration of 1.6 μg/ml (or mg/l) was measured between 2.5 and 4 hours post-dose. Conclusion: Oral levofloxacin reaches the vitreous rapidly in the uninflamed phakic eye. Levels did not reach MIC90 for the commonest infecting organisms. Nevertheless, levofloxacin would be expected to be active against a higher proportion of infecting organisms than either ciprofloxacin or ofloxacin.